Perception of health personnel and patients about hospital noise (European Journal of Health Research, 2023)
Acoustic pollution and noise have a direct relationship with health. Despite the fact that in Spain there are laws that legislate noise aimed at reducing the risks of its exposure among workers, in general there is no real awareness of the harmful effects it entails. That is why the aim of this work is proposed: to analyze the perception of health personnel and patients about hospital noise. For this, there was a sample of 48 individuals, between hospitalized patients and active health personnel. For the evaluation of the participants, an ad hoc survey was used. Participation was voluntary and statistical analysis was carried out using the SPSS program. The results indicate that mornings are considered the time of day with the highest rate of noise. Among the perceived causes, the visit of relatives is identified by health workers as the one with the greatest weight. On the other hand, regarding the effects of noise, the majority of professionals point out that noise has a negative impact on health, however, only 25% of patients agree with this statement. In relation to the possible measures to reduce noise and improve the rest of the patients, both the professionals and the patients themselves, indicate that the majority use individual rooms. In conclusion, the multiple factors that are linked to excessive noise in the hospital environment and the negative repercussions of this type of pollution for both patients and workers stand out.
Keywords: noise; noise pollution; hospital environment; decibels